Seroprevalence of West Nile virus (WNV) infection among febrile patients attending selected hospitals in Kaduna state, Nigeria - J.A. Ma'aji; O.S. Olonitola; E.E. Ella (Scientific African, 2020)
West Nile virus (WNV) is the most widespread virus among flaviviruses and the study was to determine the seroprevalence and detect West Nile virus among febrile patients attending selected hospitals in Kaduna metropolis, Nigeria. A total of one hundred and thirty five (135) blood samples were collected from consenting patients and the sera obtained and screened for WNV IgM antibodies using Enzyme Linked Immunosorbent Assay (ELISA). West Nile Virus Immunoglobulin M (IgM) antibody was detected in 7(5.2%) patients with those from Kaduna Central and Kaduna South Senatorial districts recording a prevalence of 3.0% and 2.2% respectively. In all, males had higher prevalence (3.7%) as compared to the females (1.5%). Patients aged 31–50 years as well as the married had the higher cases. Those that are educated had higher prevalence than the less educated. However, the study did not establish any statistically significant association (P > 0.05) between sex, age, marital status or educational level of the patients. The patients with no defined regular work (including students) had the highest prevalence (3.0%) followed by civil servants (1.5%). The selected factors Risk factors such as blood transfusion, cancer patients and those on cancer chemotherapy, hypertensive and the diabetic had varying percentage incidence of 10.5, 20.0, 33.3, 7.1 and 9.5. Similarly improper use of mosquito nets remain a risk to the infection. Prominent symptoms include headaches (6.42%), drowsiness (5.88%), body weakness (6.31%) and vomiting (6.09). The study demonstrated a serological evidence of WNV infection in the study area with a prevalence of 5.2%. It therefore highlight the need to include screening for the West Nile virus in cases of febrile fever in the study area.